SUBSITUSI TEPUUNG TERIGU DENGAN UBI UNGU KUKUS PADA PEMBUATAN KUE BINGKE - hartono, Hartono (Jurnal Sains Pertanian Equator, 2019)
This research aims to find the best substitution of wheat flour with steamed purple sweet potato in the making of bingke cake and to obtain purple bingke composition that is most liked by consumers. This study used a randomized block design (RBD) of one factor, that was the ratio of formulation between wheat flour and steamed purple sweet potato repeated 4 times with 6 levels. The observed parameters were water content, total dissolved solids (TDS), protein content, and sensory. The data obtained were analyzed using ANOVA with 5% significance, with further testing using Duncan"™s Multiple Range Test (DMRT) with a level of 5%. The results showed that bingke with 50g of purple sweet potato and 0g of wheat flour, with water content of 46,91%, total dissolved solids of 18,18 °brix, protein content of 5,27%. The sensory characteristics of purple sweet potato were color 3,87 (quite like to like), texture 3,87 (quite like to like), sweetness 3,97 (quite like to like), with the level of pleasure 4.17 (like to really like). Keywords : cake, flour, substitution, purple sweet potato.